How Does the Starting Order in the First and Second Run Affect the Final Rank in the FIS World Cup Giant Slalom? - Björklund, Glenn; Swarén, Mikael (Frontiers in Sports and Active Living, 2022)
The aim of this study was to determine the impact of run 1 and 2 for overall rank in Giant Slalom. Data from 15 seasons (2005/2006-2019/2020) including and unique starts for women (n = 2294) and men (n = 2328) were analysed. Skiers were grouped on final rank 1-3 (G3), 4-10 (G10) and 11 – 20 (G20) and separately analysed for women and men. A Wilcoxon signed rank test was used for comparisons between run 1 and 2, while a multi-nominal logistic regression was used to identify odds ratios (OR) associated to group rank. Women had similar run times for run 1 and 2 (p = 0.734), while men had faster times on run 2 (p < 0.001). The strongest association to G3 was during run 1 for run time (men: OR 1.06 –1.12; women: OR 1.06 – 1.11, all p < 0.01) and gate-to-gate times (men: OR 33 – 475; women: OR 81 –2301, all p < 0.001). Overall, this study demonstrates the importance of a fast first run for improving final rank and the need to increase the tempo going from the first to the second run for men.